2005
DOI: 10.3758/bf03193059
|View full text |Cite
|
Sign up to set email alerts
|

Habitual acceptance of misinformation: Examination of individual differences and source attributions

Abstract: This study identifies individuals who are habitually susceptible to accepting postevent misinformation across testing on three separate events. The results indicate that those individuals identified as habitually susceptible exhibited higher dissociation scores and less of an association between memory accuracy and confidence than did the individuals identified as nonhabitually susceptible. When they were asked to identify the source of the remembered information, similar patterns of source attributions were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
2
19
2
Order By: Relevance
“…The rate of misinformation endorsement was consistent with and even slightly higher than in previous studies (Cann & Katz, 2005;Tomes & Katz, 1997), possibly because of the additional events and the longer interval between encoding and testing (Higham, 1998).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The rate of misinformation endorsement was consistent with and even slightly higher than in previous studies (Cann & Katz, 2005;Tomes & Katz, 1997), possibly because of the additional events and the longer interval between encoding and testing (Higham, 1998).…”
Section: Discussionsupporting
confidence: 66%
“…Thus, the confidence and misinformation results further support the interpretation that arousal enhanced memory consolidation, possibly via modulation of both episodic and source memory. Ideally, future studies would examine the specific effects of arousal on source monitoring, original events, misinformation items, and the respective sources of each item (Cann & Katz, 2005). Kensinger (2007) suggested that emotion or arousal specifically enhances memory for source details that have "affective relevance" (p. 215) to emotional stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors argued that dissociation might influence some specific false memory tasks that require only misattributing the source of a presented item and not the DRM paradigm which requires both generation and misattribution of the critical lure. This argument is not consistent with the current results as we found that a measure of dissociative experiences was positively associated with a higher susceptibility to false recall (see also, Cann & Katz, 2005). In addition, DES-C scores were not associated with the activation of the critical lure.…”
Section: Discussioncontrasting
confidence: 56%
“…The first perspective focuses on the potentially interfering effect of MPI on correct retrieval of the event items (e.g., Belli, Lindsay, Gales, & McCarthy, 1994;Chandler, 1989;Eakin, Schreiber, & Sergent-Marshall, 2003;Lindsay, 1990;Paz-Alonso & Goodman, 2008;Schreiber & Sergent, 1998), which we will refer to as misinformation interference (following Belli, 1989;Chandler, Gargano, & Holt, 2001). The second perspective focuses on the potential effect of MPI in inducing false reports of the misleading items (e.g., Ayers & Reder, 1998;Blank, 1998;Cann & Katz, 2005;Higham, 1998;Lindsay, 1990;Pansky & Tenenboim, in press;Paz-Alonso & Goodman, 2008;Tousignant, Hall, & Loftus, 1986;Zaragoza & Koshmider 1989;Zaragoza & Lane, 1994), which we will refer to as suggestibility (following Chambers & Zaragoza, 2001). Obviously, the two perspectives are strongly related.…”
Section: The Misinformation Effectmentioning
confidence: 99%